A decision aid for women at increased risk for ovarian cancer. Issue 1 (1st January 2003) - Tiller, K.; Meiser, B.; Reeson, E.; Tucker, M.; Andrews, L.; Gaff, C.; Kirk, J.; Phillips, K. A.; Friedlander, M.
Abstract : This paper reviews changes that have occurred within and without the medical profession that have fostered an increasing demand for decision aids as adjuncts to practitioners' counseling to prepare patients for decision making. In the absence of data on the efficacy of ovarian cancer screening and prophylactic strategies, decisions about optimal care are difficult for both women and their doctors. Because surveillance and preventive options are an area of great uncertainty, a decision aid has been developed specifically aimed at facilitating decisions involving ovarian cancer risk management options. This was achieved by reviewing and integrating the available literature on models of medical decision making, patient preferences for information and involvement in decision making, the utility of decision aids, and management options for ovarian cancer risk. Findings indicate that patients wish to be informed participants in the decision-making process and that decision aids are an acceptable and effective method of providing quality information in a format that facilitates an inclusive model of shared decision making. A decision aid designed for women at increased risk of ovarian cancer that facilitates informed decision making may be a valuable addition to patient support. A randomized controlled trial of this type of educational material will provide timely and much needed evidence on its acceptability and efficacy.